STRUKTUR HISTOLOGI DAN JUMLAH SEL GOBLET PADA SEDIAAN HISTOPATOLOGIS RADANG USUS BESAR DENGAN PEWARNAAN HEMATOXYLIN-EOSIN (HE) DAN PERIODIC ACID-SCHIFF (PAS) - Chairani Chairani; Fitra Wahyuni; Tofrizal Tofrizal; Salsabila Salsabila (Ensiklopedia of Journal, 2022)
Abstract: Goblet cells and the mucus they produce serve as an important barrier to prevent pathogens invading the mucosal tissue that can cause inflammation. In the inflamed tissue, will have changed in the structure and number of goblet cells. Hematoxylin-Eosin (HE) staining is a standard stain used to examine the histological structure of tissues while Periodic Acid-Schiff (PAS) is a histological stain other than HE that can stain carbohydrates and carbohydrate-rich macromolecules. The purpose of this study was to observe differences in the structure and number of goblet cells in the inflammatory colon using HE and PAS staining. This study used 27 samples of paraffin block of rat colon tissue which were divided into three groups, namely the normal group, acute intestinal inflammation, and chronic intestinal inflammation. The tissue samples were then stained with HE and PAS staining techniques. In this study, statistical analysis of an independent t-test and Mann-Whitney test was used to observe differences in the number of goblet cells in inflammatory colon tissue using HE and PAS staining in each group. This study concludes that the number of goblet cells that can be observed in inflammatory colon tissue using HE and PAS staining is significantly different with a p-value <0.05 where the average number of goblet cells using PAS staining is higher than using HE.Keywords: goblet cells, inflammatory colon, Hematoxylin-Eosin, Periodic Acid-Schiff.